Comparative economics of indigenous Kulagar and Integrated Farming Systems under coastal agro-ecosystem of Goa - BEHERA, U K; PARAMESHA, V; KUMAR, AMIT (The Indian Journal of Agricultural Sciences, 2020)
A study was conducted during 2016-17 at coastal ecology of Goa comprising farmers from different villages in North Goa and South Goa to assess the economic benefit of two prevalent types of farming systems. In this study, Integrated Farming System (IFS) and Indigenous Kulagar Farming Systems (IKFS) were compared; and overall it was revealed that both are useful in enhancing the livelihood of small and marginal farmers, attracted the rural youth through generation of additional income and employment opportunities. There is need to modify the IKFS with integration of high value crops and having high market demand to make the system more remunerative and attractive. The IFS and IKFS have been the mainstay of economy and livelihood of farmers in Goa state. The mosaic structure of Kulagar with variety of crops offers a scope for inbuilt biodiversity as an index of sustainability in agriculture. Besides, both systems are climate resilient and proved potential for adaptation and mitigation to climate change. IFS and IKFS may be promoted in large scale in coastal agro-ecosystem in other parts of the country as an important strategy for enhancing livelihood and climate resilience in agriculture.